Pengaruh Perkembangan Bank Syariah sebelum dan Saat Covid-19 - Hanifah Anisya Yualita; Anzu Elvia Zahara; Nurfitri Martaliah (Jurnal Ekonomi Islam, 2023)
This study aims to determine the difference between the Non-Performing Financing (NPF) ratio and the Ratio of Operating Income to Operating Expenses (BOPO) in Islamic Banks before and during Covid-19. The type of research used in this study is a descriptive type of research with a quantitative approach, the object of this study is Non-Perfoming Financing (NPF) as a variable (X1) and Operating Expenses Operating Income (BOPO) as a variable (X2). The time of this study was conducted from September 2, 2022 to September 14, 2022. The data source used in this study is secondary data sourced from the Financial Services Authority website through the OJK website. The population of this study is all shari'a banks registered with the Financial Services Authority (OJK). The sampling method used in this study was purposive sampling. The results of this study are that there is no difference in financing performance at shari'a banks before and during Covid-19. Based on a significance value of 0.562 with a profitability of 0.000 > 0.05, so that the NPF value before Covid-19 and during Covid-19 did not experience a significant difference. Based on the significance value of 0.577 with a profitability of 0.000 > 0.05, so that the result is no difference in the ratio of operating expenses to operating income (BOPO) in sharia banks before Covid-19 and during Covid-19 did not experience a significant difference.